Microwave-Assisted Ablation Improves the Prognosis of Patients With Hepatocellular Carcinoma Undergoing Liver Resection. (6th July 2018) - Shen, Haiyuan; Zhou, Shu; Lou, Yun; Gao, Yangjuan; Cao, Shouji; Wu, Du; Li, Guoqiang
Objective: We evaluated microwave-assisted liver resection for hepatocellular carcinoma. Patients and Methods: We enrolled 79 patients in this study, and microwave ablation was used for liver resection. Patients were randomized to group A (50.6%; n = 40), liver resection without microwave ablation, or group B (49.4%; n = 39), liver resection performed using microwave ablation. Data were analyzed for statistical significance. Results: Of the participants enrolled, 60 were male, and the participant's average age was 59.32 ± 10.34 years. The mean overall tumor diameter was 4.39 (2.00) cm, and this did not differ between groups. Intraoperative blood loss in group B was significantly less than that in group A ( P < .001). No differences were reported between the 2 groups regarding surgical time ( P = .914), postoperative morbidity ( P = .718), and late postoperative complications ( P = .409). Postoperative drainage volume for group B was less than that of group A on the first ( P = .005) and third ( P = .019) day after surgery. The time of postoperative hospitalization in group B was significantly shorter than that in group A ( P < .001). Local recurrence was noted in 18.99% of cases (n = 15) in group B, which is less than that of group A ( P = 0.047), while in group B distant metastasis is less but not statistically significant ( P = 0.061). The 1-year and 3-year cumulative survival rates were 57% and 93.7%, respectively. Conclusions: The curative effects of liver resection combined with microwave ablation during operation are superior to only liver resection in the treatment of primary liver cancer.